2023
DOI: 10.1525/elementa.2022.00129
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the coupled mercury-halogen-ozone cycle in the central Arctic during spring

Abstract: Near-surface mercury and ozone depletion events occur in the lowest part of the atmosphere during Arctic spring. Mercury depletion is the first step in a process that transforms long-lived elemental mercury to more reactive forms within the Arctic that are deposited to the cryosphere, ocean, and other surfaces, which can ultimately get integrated into the Arctic food web. Depletion of both mercury and ozone occur due to the presence of reactive halogen radicals that are released from snow, ice, and aerosols. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 158 publications
2
1
0
Order By: Relevance
“…Firstly, the sea-ice-covered central Arctic Ocean is the location where springtime AMDEs occur; therefore, it receives and stores large amounts of Hg(II) 8 , 33 , 46 . This is supported by springtime GEM observations (March–May) during this expedition, which showed that AMDEs were ubiquitous over the central Arctic 34 . According to a modeling study, only 4% of deposited Hg(II) over the central Arctic Ocean is re-emitted before snowmelt due to the presence of halides that inhibit Hg(II) photoreduction 34 .…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Firstly, the sea-ice-covered central Arctic Ocean is the location where springtime AMDEs occur; therefore, it receives and stores large amounts of Hg(II) 8 , 33 , 46 . This is supported by springtime GEM observations (March–May) during this expedition, which showed that AMDEs were ubiquitous over the central Arctic 34 . According to a modeling study, only 4% of deposited Hg(II) over the central Arctic Ocean is re-emitted before snowmelt due to the presence of halides that inhibit Hg(II) photoreduction 34 .…”
Section: Resultssupporting
confidence: 79%
“…This is supported by springtime GEM observations (March–May) during this expedition, which showed that AMDEs were ubiquitous over the central Arctic 34 . According to a modeling study, only 4% of deposited Hg(II) over the central Arctic Ocean is re-emitted before snowmelt due to the presence of halides that inhibit Hg(II) photoreduction 34 . In summer, this previously deposited Hg(II) is transferred to the surface ocean with snow and sea-ice melt 47 , resulting in a large Hg load in surface seawater of the MIZ.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation